EDUCATION SYSTEM AND ENGLISH LANGUAGE TEACHING IN THE PHILIPPINES: IMPLICATIONS FOR INDONESIAN EFL LEARNING - Dedi Turmudi; Bonjovi Hassan Hajan (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2020)
The Philippines is held as one of the largest English-speaking countries worldwide with most of its people possessing at least some degree of fluency in the target language. The prestige of the English language in this country has attracted the attention of many foreign students including Indonesian. In this paper, we aimed to discuss the education system and the English language teaching (ELT) in the Philippines so that practical insights can be gained to reflect on Indonesian EFL learning. To this end, we first described how the Philippine education system looks like and how the English language is taught in schools from elementary to tertiary level. We then explored some prevailing challenges surrounding the ELT, and established links relating the benefits of learning English in this country to Indonesian EFL context. Drawing on qualitative approach, we realized our research objectives by carefully selecting sources and data through critical review of articles from journals, books, websites, and other reliable sources retrieved online. Ultimately, we conducted this inquiry to find out answers so that some lessons learned can be adopted to make ELT in Indonesia better and more resilient since Indonesia remains left behind in the spectrum of English literacy.